Implementation of Voltage Stabilizers on Solar Cell System Using Buck-Boost Converter - Irgi Achmad; Anggara Trisna Nugraha (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
Electricity is one of the basic needs of modern human life and is already so integrated into everyday life. This is understandable given the coal's ample resources. Another factor that influences the growth of coal use is that coal plants are designed asa basic burden because the price of coal is relatively cheaper. However, coal's existence as fuel for power plants is on the decline and is not renewables. One of the applications of renewable energy potential is solar power generation technology. On this system using solar panels using 30 wp power. Solar dependence on the environment affects the change in output values in hybrid plant systems, resulting in easy damage to both domestic and industrial appliances or in battery storage systems, so a mechanism is needed to stabilize the output voltage supplied to the battery or load. So, out of this renewable energy potential, it creates innovation Implementation of Voltage Stabilizers on Solar Cell System Using Buck-Boost Converter. Aided by current and voltage sensors controlled by arduino uno so that they can insulate input and output from buck-boost converter. Results from the testing of this device indicate that the buck-boost converter is able to stabilize output output from solar panels with a 14.4 volt set of points. The average efficiency obtained at buck-converter converter testing at buck mode is 85.4 %. On boost mode is 80%. On buck-boost mode is 79.2%.